Pencemaran Nama Baik di Era Digital: Analisis Hukum Normatif terhadap Pilihan Jalur Penyelesaian Sengketa di Indonesia - Simanjuntak, Predderics Hockop (JUNCTO: Jurnal Ilmiah Hukum, 2025)
Defamation has become an increasingly complex legal issue, particularly with the rapid growth of information technology and social media. This study aims to analyze the resolution of defamation disputes through criminal law, civil law, and restorative justice approaches in Indonesia. Criminal provisions are regulated in the Criminal Code and the Electronic Information and Transactions Law, while civil remedies allow victims to sue under Article 1365 of the Indonesian Civil Code. Meanwhile, the restorative justice approach offers an alternative resolution emphasizing recovery and reconciliation between the offender and the victim outside of litigation. This research employs a normative legal method with statutory and conceptual approaches. The findings indicate that although legal frameworks exist, their implementation faces challenges such as limited law enforcement capacity, low public legal awareness, and the imbalance between individual protection and freedom of expression. This research contributes to both theoretical and practical understanding of dispute resolution in defamation cases and encourages a more proportional and humane application of the law.